1998
DOI: 10.1080/10408699891274246
|View full text |Cite
|
Sign up to set email alerts
|

Reinterpretation of Microbial Survival Curves

Abstract: The heat inactivation of microbial spores and the mortality of vegetative cells exposed to heat or a hostile environment have been traditionally assumed to be governed by first-order reaction kinetics. The concept of thermal death time and the standard methods of calculating the safety of commercial heat preservation processes are also based on this assumption. On closer scrutiny, however, at least some of the semilogarithmic survival curves, which have been considered linear are in fact slightly curved. This … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

5
425
0
22

Year Published

2004
2004
2017
2017

Publication Types

Select...
4
3
1

Relationship

0
8

Authors

Journals

citations
Cited by 697 publications
(460 citation statements)
references
References 0 publications
5
425
0
22
Order By: Relevance
“…Hence, all spores in the clumps need to be inactivated prior to the destruction of colony forming ability of the clump (Adams and Moss 1997;Furukawa et al 2005). The effect could also be due to the heterogeneous sub-populations of spores (dormant, germinated and inactivated) differing in their physiological state during heat treatment and become resistant within a highly extreme resistant sub-population (Peleg and Cole 1998). The lag phase in spore inactivation pattern revealed that there was a small decrease in the concentration of spores and the linear decline phase show that specific death rate was constant.…”
Section: Resultsmentioning
confidence: 99%
“…Hence, all spores in the clumps need to be inactivated prior to the destruction of colony forming ability of the clump (Adams and Moss 1997;Furukawa et al 2005). The effect could also be due to the heterogeneous sub-populations of spores (dormant, germinated and inactivated) differing in their physiological state during heat treatment and become resistant within a highly extreme resistant sub-population (Peleg and Cole 1998). The lag phase in spore inactivation pattern revealed that there was a small decrease in the concentration of spores and the linear decline phase show that specific death rate was constant.…”
Section: Resultsmentioning
confidence: 99%
“…The cumulative form of Weibull frequency distribution model was used to describe Campylobacter survival kinetics in water as it is suitable for quantifying Page 5 / 19 bacterial survival for both log and non-log linear survival curves. The Weibull model has largely been used to describe bacterial inactivation by thermal and nonthermal processes as stress resistance of a microbial population often follows a Weibull distribution (Cunhan et al, 1998;Peleg and Cole, 1998;Fernandez et al, 1999;van Boekel, 2002;Corradini and Peleg, 2003;Virto et al, 2005;Hajmeer et al, 2006). We used a logarithm decimal form of Weibull defined as follows (Mafart et al, 2002;van Boekel, 2002):…”
Section: Campylobacter Infectionsmentioning
confidence: 99%
“…Based on these types of variations, Peleg proposed a model for microbial inactivation, known as Peleg Model (Peleg 1995;Peleg and Cole 1998) which represents the field strength and survival fraction as…”
Section: Model 2 (Peleg Model)mentioning
confidence: 99%
“…This model is a mathematical equation based on Weibull distribution function (Peleg and Cole 1998;Van Boekel 2002) which describes the survival curves non-logarithmically as…”
Section: Model 4 (Weibull Distribution Model)mentioning
confidence: 99%
See 1 more Smart Citation